The market for corporate control and dividend policies: Cross-country evidence from M&A laws - Glendening, Matt; Khurana, Inder K.; Wang, Wei (Journal of International Business Studies, 2016)
This article examines the association between the market for corporate control and firm dividend policies. Specifically, we examine changes in firms’ dividend payouts following a plausibly exogenous shock to the threat of takeover with the staggered initiation of country-level merger and acquisition (M&A) laws. Using a global sample of firms across 34 countries, we find that both the likelihood and the amount of dividends decrease significantly after the initiation of an M&A law in a country. Our cross-sectional analyses indicate that the negative effect of M&A laws on dividend payouts is amplified in countries where the institutional environment enables M&A laws to improve the takeover market and for firms that could readily use internal capital to finance growth opportunities. Moreover, this negative effect is attenuated for firms with already sufficient monitoring of managers. These findings suggest that the enactment of M&A laws, by strengthening the market for corporate control, lowered the need for firms to convey their commitment to shareholders’ interests through costly dividend payments, especially when the threat of takeover prompted by M&A laws is likely to serve as an effective disciplinary mechanism.